Social Sector Spending in a Panel of Countries - Baqir, Reza (IMF Working Papers; Working Paper, 2002)
This paper presents evidence on the political and economic determinants of social sector spending from a panel dataset. The principal finding is that democratization in countries, as measured by within-country variation in subjective indices of democracy, is a significant predictor of government spending on education and health. The relationship is robust to controlling for a variety of factors and the estimated magnitudes suggest that an increase from the lowest to the highest rating for democracy for a country is associated with approximately 1 percent more central government spending and 3 percent more general government spending in social sectors, as a percent of GDP.